Pharmaceutical Industrial Waste Regulation in Five Countries in Asia - Luthfia Azzahra; Nyi Mekar Saptarini (Indonesian Journal of Pharmaceutics, 2021)
The pharmaceutical industry produces a various toxic wastes. Generated waste increases the risk of environmental and ecosystem pollution. It is necessary to have proper waste management to prevent waste pollution to the environment. In 1999, WHO published “Guidelines for the Safe Disposal of Unwanted Pharmaceuticals in and after Emergencies”, that contain treatments and safe disposal method, which is appropriate for any country. Many countries had developed and published regulations and guidelines on waste management. This article aimed to review the handling of pharmaceutical industrial waste in five countries in Asia. This review included studies from ProQuest, Crossref, and Google Scholar.  The pharmaceutical industries in Indonesia, India, Japan, Thailand, and China has their own state regulations in order to protect the environment. They also had implemented pharmaceutical industrial waste management following their regulation and guidelines. The method used to treat the waste is similar with WHO guideline. Some factors affecting the country regulations are the insufficient of land and waste management facilities, lack of awareness, low penalties, limited infrastructures, lack of waste testing facilities. The challenge in the future to handle pharmaceutical waste are increasing waste volume, decreasing land for waste management, sewer methods may contaminate water, possible air pollution due to incineration, so it is necessary to have more advanced methods in waste management that are safe for the environment and humans.Keywordz: Industry, Pharmaceutical, Waste Regulation, Asia